Zero Waste Education Organic Waste Treatment for Students of SD N Petompon 3 - Irene Nindita Pradnya; Maulida Zakia; Zuhriyan Ash Shiddieqy Bahlawan; Kakalia Putri Auralita; Achmad Wikandaru; Daffa Nur Muhammad (Journal of Clean Technology, 2024)
Improper waste management at SDN Petompon 3 Semarang has led to inadequate sanitation and a lack of environmental awareness among students. This community service initiative aimed to address these issues by educating 5th and 6th-grade students on organic waste processing through the utilization of Black Soldier Fly (BSF) larvae. The program introduced a hands-on approach where students learned to sort, manage, and convert organic waste into value-added products such as animal feed and organic fertilizer. Additionally, the program incorporated entrepreneurship training, equipping students with basic skills in packaging, branding, and marketing to promote sustainable small-scale enterprises. The activities included stakeholder coordination, infrastructure preparation, environmental education, and product processing workshops. Results showed improved student participation, increased environmental knowledge, and measurable growth in maggot biomass and waste decomposition rates over 30 days. This integrated program not only enhanced environmental cleanliness at the school but also fostered early environmental stewardship and entrepreneurial skills among students, contributing to sustainable waste management and community empowerment.